PENGARUH GENDER DAN KEYAKINAN TERHADAP PERILAKU SOCIAL AND ENVIROMENTAL ACCOUNTING (SEA) - Swandini, Witantri Dwi (Jurnal Studi Gender dan Anak, 2022)
This study aims to of determine how the influence of gender and beliefs on the behavior/attitude of social and environmental accounting (SEA). Research on social and environmental accounting (SEA) so far has concentrated more on corporate disclosure. However, research that investigates how a person's attitude towards social and environmental accounting is rarely discussed. SEA is accounting information that develops the relationship between business and society, community, and nature. In addition, SEA also studies the concept of sustainability, where according to SEA, natural resources need to be preserved for the sustainability of future generations. The current generation of young people is seen as having no concern for social issues and environmental sustainability. This may be due to factors of belief and cultural background. This study examines the effect of gender and beliefs on SEA attitudes. Four dimensions of belief (permanent ability, fast learning, simple knowledge, and specific knowledge) were adopted from Schommer (2005). The results of the study revealed that gender differences did showed an influence on their attitudes towards SEA. Respondents who believe in the importance of social and environmental accounting tend to have more positive attitudes towards environmental sustainability. Keywords: Gender, Belief, Attitude Towards, Social and Enviromental Accounting